Peningkatan Motivasi Intrinsik dalam Belajar Materi Interaksi Manusia dengan Lingkungan Melalui Penerapan Teknik Truth or Dare Questions - Mohamad Jaidi (Journal on Education, 2021)
The purpose of this study was to find out how the teacher's activities in applying the Truth or Dare Questions technique to learning the Human-Environmental Interaction material, to find out how the Teacher's Activity in applying the Truth or Dare Questions technique to learning the Human-Environmental Interaction material, and to find out how to apply the technique. Truth or Dare Questions to increase intrinsic motivation in learning the material on Human-Environmental Interaction in Grade 5 students of SD Negeri Kendangsari I/276 Surabaya. The research was conducted with a two-cycle action mechanism. And based on the results of data analysis, it can be concluded that most students have grown and developed their motivation, which is 75%. This is evidenced by the great enthusiasm of students towards the teaching and learning process that takes place from the beginning to the end of the activity. This pattern of behavior marks an increase in students' intrinsic motivation to study the Human-Environmental Interaction material with the application of the Truth or Dare Questions technique which focuses on students' independence in finding answers to the problems posed by the questions, and on the existence of the teacher as a facilitator in the classroom. The stages of activities carried out by students during the teaching and learning process have a positive impact on increasing students' intrinsic motivation. This is indicated by the increasing percentage of intrinsic motivation classically from Pre Cycle (52%) Cycle I (64%) to Cycle II (75%). The existence of a hypothesis about the effectiveness of the application of the Truth or Dare Questions technique on increasing students' intrinsic motivation to study the material on Human Interaction with the Environment Class 5 SD Negeri Kendangsari I/276 Surabaya is indirectly proven in this study.